PENGAKTUALAN UNSUR MITOLOGI DALAM PUlSl GOENAWAN MOHAMAD DAN SAPARDI DJOKO DAMONO*) - Burhan Nurgiyantoro, Burhan Nurgiyantoro (Jurnal Cakrawala Pendidikan, 2016)
lndoiiesiaii literary writing today appears to contain consi-derable adoption and actualization of mythological stories coming fiom various parts of the country and fiom abroad. Goenawan Mo-hammad and Sapardi Djoko Damono are the foremost Indonesian poets now considered ’pioneers" in actualizing mythological stories in poetry. A study therefore aims at showing ( I ) the mythological elements actualized in their poetly, (2) the forms of the hypograms of those elements, and (3) tlie functions of tlie actualization of those elements. The sources of the data for this study are Goellawan’s and Sapardi’s poems published in an anthol- OL3’. The result oftlie study shothat mythological elements actualized in the poelns come from various mythologies in the country which include stories of trj.crrPiagn, ji, Anglingdatma, and Btrhutl Trrntrh./cru ain d from those abroad which include stories of Iskandar Zulharnain, Serihu Sulu Molarii, and classic Greece. Though relatively not many, the poems are considered important as they reappear in later publications and the titles of some are even used for those publications. The poems containing elements of mythological stories as hypograms generally continue to use the conventions of the mythology transfol nedI.t indicates the two poets’ acceptance and response to mythology; they treat it as it is as sotilething factual. The mythological elements actualized in the poelns are made to fuliction either as materials to support the theme or as materials for comparison, symbolization, and cul-tural reference. Their use as support to the theme can be regarded as offering another form ofstorytelling and their use in the other ways can be regarded as enrichment of poetical expressions.